Be a Better Chooser - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet lists the factors to take into consideration when deciding upon a color scheme for a home's exterior. These include the colors of the window screen frames, porch ceilings, doors, and even the chimney. Describes several home exteriors for inspiration and lists color combinations that are guaranteed to look aesthetically pleasing. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Architecture, Domestic; Paint materials; Exterior walls; Dwellings--Maintenance and repair; Color in architecture; Varnish industry; Paint industry and trade; Advertising--Paint